Altered GABAergic, glutamatergic and endocannabinoid signaling is accompanied by neuroinflammatory response in a zebrafish model of social withdrawal behavior - Perdikaris, Panagiotis; Dermon, Catherine R. (Frontiers in Molecular Neuroscience, 2023)
Introduction Deficits in social communication are in the core of clinical symptoms characterizing many neuropsychiatric disorders such as schizophrenia and autism spectrum disorder. The occurrence of anxiety-related behavior, a common co-morbid condition in individuals with impairments in social domain, suggests the presence of overlapping neurobiological mechanisms between these two pathologies. Dysregulated excitation/inhibition balance and excessive neuroinflammation, in specific neural circuits, are proposed as common etiological mechanisms implicated in both pathologies. Methods and Results In the present study we evaluated changes in glutamatergic/GABAergic neurotransmission as well as the presence of neuroinflammation within the regions of the Social Decision-Making Network (SDMN) using a zebrafish model of NMDA receptor hypofunction, following sub-chronic MK-801 administration. MK-801-treated zebrafish are characterized by impaired social communication together with increased anxiety levels. At the molecular level, the behavioral phenotype was accompanied by increased mGluR5 and GAD67 but decreased PSD-95 protein expression levels in telencephalon and midbrain. In parallel, MK-801-treated zebrafish exhibited altered endocannabinoid signaling as indicated by the upregulation of cannabinoid receptor 1 (CB1R) in the telencephalon. Interestingly, glutamatergic dysfunction was positively correlated with social withdrawal behavior whereas defective GABAergic and endocannabinoid activity were positively associated with anxiety-like behavior. Moreover, neuronal and astrocytic IL-1β expression was increased in regions of the SDMN, supporting the role of neuroinflammatory responses in the manifestation of MK-801 behavioral phenotype. Colocalization of interleukin-1β (IL-1β) with β2-adrenergic receptors (β2-ARs) underlies the possible influence of noradrenergic neurotransmission to increased IL-1β expression in comorbidity between social deficits and elevated anxiety comorbidity. Discussion Overall, our results indicate the contribution of altered excitatory and inhibitory synaptic transmission as well as excessive neuroinflammatory responses in the manifestation of social deficits and anxiety-like behavior of MK-801-treated fish, identifying possible novel targets for amelioration of these symptoms.